Periphere Räume in der Amerikanistik - Pisarz-Ramírez, Gabriele; Adrian Wöll, Steffen (2019)
This volume addresses the notion of the periphery as a concept in cultural studies and the discursive and narrative dimensions of peripheral spaces. Peripheral spaces are defined as those spaces that are controlled and directed only to a limited extent from the center.